Conspecific versus heterospecific gene exchange between populations of Darwin's finches - Grant, Peter R. (The Royal Society, 2010)
This study addresses the extent and consequences of gene exchange between populations of Darwin's finches. Four species of ground finches (Geospiza) inhabit the small island of Daphne Major in the centre of the Galápagos archipelago. We undertook a study of microsatellite DNA variation at 16 loci in order to quantify gene flow within species owing to immigration and between species owing to hybridization. A combination of pedigrees of observed breeders and assignments of individuals to populations by the program Structure enabled us to determine the frequency of gene exchange and the island of origin of immigrants in some cases. The relatively large populations of Geospiza fortis and G. scandens receive conspecific immigrants at a rate of less than one per generation. They exchange genes more frequently by rare but repeated hybridization. Effects of heterospecific gene flow from hybridization are not counteracted by lower fitness of the offspring. As a result, the standing genetic variation of the two main resident populations on Daphne Major is enhanced to a greater extent by introgressive hybridization than through breeding with conspecific immigrants. Immigrant G. fuliginosa also breeds with G. fortis. Conspecific immigration was highest in the fourth species, G. magnirostris. This species is much larger than the other three and perhaps for this reason it has not bred with any of them. The source island of most immigrants is probably the neighbouring island of Santa Cruz. Evolutionary change may be inhibited in G. magnirostris by continuing gene flow, but enhanced in G. fortis and G. scandens by introgressive hybridization.